STUDI VARIASI PELAFALAN FONEM /R/ DAN GANGGUAN FONOLOGI PADA PENDERITA CADEL - fathunah, Nada; Siagian, Irwan (Peneliti.net, 2023)
This study aims to investigate the pronunciation variations of the phoneme /r/ and phonological disorders in individuals with lisp disorders. The phoneme /r/ is one of the consonant phonemes that often experiences pronunciation variations in the general population, but these variations seem to be more complex in individuals with phonological disorders. This study involved observation and analysis of the pronunciation of the phoneme /r/ in a number of lisp sufferers with various degrees of severity of phonological disorders. The results of this study are expected to provide a better understanding of variations in the pronunciation of the phoneme /r/ in people with slurred speech and the contribution of phonological disorders to these variations.